Motivations of the Ethical Consumer - Freestone, Oliver M. (Journal of business ethics, 2008)
There are strong indications that many consumers are switching towards more socially and environmentally responsible products and services, reflecting a shift in consumer values indicated in several countries. However, little is known about the motives that drive some toward, or deter others from, higher levels of ethical concern and action in their purchasing decisions. Following a qualitative investigation using ZMET and focus group discussions, a questionnaire was developed and administered to a representative sample of consumers; nearly 1,000 usable questionnaires were collected. The degree of awareness, concern and action regarding 16 ethical issues was quantified, using a measure developed from the Stages of Change concept within the Transtheoretical model. Motivations for ethical behaviour, in relation to each individual’s most salient ethical issue, were investigated using initially 22 motive statements within the framework of the Decisional Balance Scale (DBS). The findings suggest that the DBS and Stages model have an explanatory value within the ethical decision-making context, and that the motives identified do reflect the Decisional Balance Constructs. Indeed the study suggests that respondents’ motivational attitudes are a function of their stage of ethical awareness, concern and action. Therefore, the Decisional Balance Scale may well prove useful for designing appropriate interventions and communications to facilitate movement towards more ethical decision-making. These findings yield strategic insight for communicating messages to ethical consumers and for better understanding their purchasing decisions.